2013
DOI: 10.1016/j.febslet.2013.01.049
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor early B‐cell factor 1 regulates bone formation in an osteoblast‐nonautonomous manner

Abstract: Early B-cell factor 1 (Ebf1) is a transcription factor whose inactivation in all cells results in high bone mass because of an increase in bone formation. This observation suggests Ebf1 may be an inhibitor of osteoblast differentiation. To test this contention, we analyzed Ebf1 pattern of expression and function in osteoblasts ex vivo and in vivo through osteoblast-specific inactivation in the mouse. We show here that in vivo deletion of Ebf1 in osteoblast progenitors does not affect osteoblast differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
(29 reference statements)
1
5
0
1
Order By: Relevance
“…Bone marrow from 18-and 90-wk-old Prx1-Cre;Ebf1 f/f mice showed no gross hematopoietic or bone abnormalities (Supplemental Fig. S5A-E), consistent with previous studies of mice deficient for Ebf1 exhibiting a subtle or no skeletal phenotype (Hesslein et al 2009;Zee et al 2013). Histological analysis of femurs in newborn and 1-wk-old Prx1-Cre;Ebf1 f/f Ebf3 f/f ;CXCL12-GFP mice in which Ebf1 and Ebf3 were inactivated in mesenchymal cells, including CAR cells, revealed that although the trabecular bone mass was somewhat increased, bone marrow cavities were formed (Fig.…”
Section: Car Cells Exhibiting a Normal Morphology Are Present But Hssupporting
confidence: 90%
“…Bone marrow from 18-and 90-wk-old Prx1-Cre;Ebf1 f/f mice showed no gross hematopoietic or bone abnormalities (Supplemental Fig. S5A-E), consistent with previous studies of mice deficient for Ebf1 exhibiting a subtle or no skeletal phenotype (Hesslein et al 2009;Zee et al 2013). Histological analysis of femurs in newborn and 1-wk-old Prx1-Cre;Ebf1 f/f Ebf3 f/f ;CXCL12-GFP mice in which Ebf1 and Ebf3 were inactivated in mesenchymal cells, including CAR cells, revealed that although the trabecular bone mass was somewhat increased, bone marrow cavities were formed (Fig.…”
Section: Car Cells Exhibiting a Normal Morphology Are Present But Hssupporting
confidence: 90%
“…EBF proteins are composed of five domains; DNA binding domain (DBD), immunoglobulin‐like plexins transcription factor (IPT), atypical HLH, transactivation I domain (TSI), and transactivation II (TSII) domain and are originally discovered in rodents as a protein that regulates the differentiation of B‐lymphocyte (Crozatier, Valle, Dubois, Ibnsouda, & Vincent, ). Our previous studies in addition to others demonstrated the importance of EBF for tissue specification, differentiation, and cell movements during development of nervous, adipose, muscular, and skeletal tissues as well as feathers and bone marrow (El‐Magd, Saleh, El‐Aziz, & Salama, ; El‐Magd, Sayed‐Ahmed, Awad, & Shukry, ; Moruzzo et al, ; Seike, Omatsu, Watanabe, Kondoh, & Nagasawa, ; Tolkin & Christiaen, ; Zee et al, ).…”
Section: Introductionmentioning
confidence: 70%
“…specification, differentiation, and cell movements during development of nervous, adipose, muscular, and skeletal tissues as well as feathers and bone marrow El-Magd, Sayed-Ahmed, Awad, & Shukry, 2014;Moruzzo et al, 2017;Seike, Omatsu, Watanabe, Kondoh, & Nagasawa, 2018;Tolkin & Christiaen, 2016;Zee et al, 2013).…”
mentioning
confidence: 99%
“…EBF1 is a negative regulator of bone mass. ( 35,38,39 ) However, the cell types responsible for this phenotype has not been identifed, as conditional deletion of Ebf1 with Lepr‐Cre or Runx2‐cre did not alter bone properties, (38,39 ) whereas global or Prrx1‐Cre ‐mediated deletion of Ebf1 increased trabecular bone mass. ( 35,40 ) It will be important to determine if conditional inactivation of Ebf1 in PαS cells leads to improved bone properties.…”
Section: Discussionmentioning
confidence: 99%